2004
DOI: 10.1016/j.jbiomech.2003.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Maximising somersault rotation in tumbling

Abstract: Performing complex somersaulting skills during the flight phase of tumbling requires the generation of linear and angular momenta during the approach and takeoff phases. This paper investigates how approach characteristics and takeoff technique affect performance with a view to maximising somersault rotation in tumbling. A five-segment planar simulation model, customised to an elite gymnast, was used to produce a simulation which closely matched a recorded performance of a double layout somersault by the elite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…The level of hand-feet parallelism during the back projection suggest an advanced performance. Indeed, a linear back projection is important for the generation of momentum and horizontal velocity 9 . Additionally, considering that in gymnastics the upper extremities are regularly used to sustain body weight, a correct execution of all phases (above all the IHS) is necessary not only for a successful performance, but also to avoid (or reduce) macro-and micro-injuries during the execution of floor exercises 4,6,8,19,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of hand-feet parallelism during the back projection suggest an advanced performance. Indeed, a linear back projection is important for the generation of momentum and horizontal velocity 9 . Additionally, considering that in gymnastics the upper extremities are regularly used to sustain body weight, a correct execution of all phases (above all the IHS) is necessary not only for a successful performance, but also to avoid (or reduce) macro-and micro-injuries during the execution of floor exercises 4,6,8,19,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The method described in the current study may be used to collect data on a wide group of elite gymnasts of both sexes to define some "gold standard execution", with parameters related to individual anthropometric measures. Furthermore, the same technical parameters could be used in the biomechanical approaches to gymnastic performance, improving the modeling and optimizing the algorithms of execution [8][9][10][11]22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…King and Yeadon (2004) found that large linear and angular approach velocities were key for maximising rotation in tumbling and that a straight triple somersault should be possible. A straight triple somersault has now been performed in tumbling competition.…”
Section: Introductionmentioning
confidence: 99%
“…The gymnast and coach aim to maximise performance and develop training regimes and technical strategies to achieve this. Similarly most of the computer simulation research in gymnastics, jumping and landing has been aimed at improving performance (Hiley and Yeadon, 2003;King and Yeadon, 2004) and has not considered the potential injury risks. Using a gymnast to investigate different landing techniques experimentally could lead to injury.…”
Section: Introductionmentioning
confidence: 99%